Business Asset Diversification as an Implementation of the Financial Behavior of Madurese Merchants in Managing Warung Madura - Ahmad Rifai Ali Zain Rifai (CV Edujavare Publishing, 2026)
Warung Madura represents a rapidly growing micro-enterprise sector in Indonesia, managed by ethnic Madurese merchants characterized by distinct cultural values, religiosity, and a strong work ethic. However, research into the financial behavior of *Warung Madura* merchants—specifically integrating cultural values ​​with modern financial accounting perspectives—remains limited. This study aims to analyze the financial behavior of ethnic Madurese merchants in managing their *Warung Madura* businesses and to uncover the influence of cultural values ​​and religiosity on financial decision-making and business sustainability. A qualitative approach utilizing an ethnographic model was employed. Data were collected through participant observation, in-depth interviews, documentation, and cultural mapping, and subsequently analyzed using coding techniques, including open, axial, and selective coding. The results indicate that the merchants' financial behavior is shaped by values ​​such as hard work, religiosity, honesty, and kinship; these values ​​are reflected in capital management, the separation of personal and business finances, simple financial record-keeping, cash flow control, risk management, and business asset diversification. Key findings reveal that asset diversification serves as a primary strategy for strengthening capital, maintaining financial stability, and supporting business sustainability. The study’s novelty lies in its integration of a Madurese cultural ethnographic approach with modern financial accounting perspectives to explain the financial behavior of *Warung Madura* merchants, thereby enriching the study of culture-based behavioral finance within the micro-enterprise sector.